Pancreatic Adenocarcinoma Presenting as Obstructive Jaundice in A Young Woman - Evy Yunihastuti; Julius R Samban; H.M. Sjaifoellah Noer; Daldiyono Daldiyono; Unggul Budihusodo; Rino A Gani; Zubairi Djoerban (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
Pancreatic carcinoma commonly occur in patients over 60 years. It is usually manifested as abdominal pain, jaundice, and pancreatic mass. In this report, a pancreatic carcinoma occurred in young woman is presented. A surgical drainage was done and followed by Whipple resection. However, the patient passed away three month after the diagnosis.    Keywords: pancreatic carcinoma, young woman, obstructive jaundice, whipple resection